Slope Stability Evaluation based on Empirical Methods and it’s Potential Remedy at Lesser Himalayan Zone (A Case Study of Bhalam-Hill Slope, Kaski) - Baral, Prakash (Journal of Advanced Academic Research, 2023)
The study area lies in Bhalam, Kaski district nearly 2 km from Batulechour main district road network near Gandarva community residing near Kali Khola river. The study area is comprises of several lithological factors. Field observation, sampling, lab analysis, geological survey with GPS, compass, geological hammer and tape are the main methods utilize to evaluate slope stability and possibility of failure in the study area. From the study it is found that there are few major discontinuities which play vital role in determining slope failure around the study area. The major failure due to discontinuity are planar failure, wedge failure and somewhere block failure. High ground water table approximately 0.06m, steep slope varying from 25° to 60°, improper road cutting, weathering of rock mass are major factor contributing to rock fall and landslide in the study area. The study also shows FOS<1(0.937 and 0.569) at two different places which is most critical and make slope unstable. SMR is calculated on the basis of RMRb, GSI is calculated on the basis of RQD and UCS is calculated on the basis of empirical methods which uses pulse velocity and porosity chart for determining related equation. The calculated value of RMRb, SMR and FOS shows less stability of study area along Bhalam-Batulechour road section near Kali- Khola river with possibility of impact on Bhalam road bridge and two lane road section. There need a corrective measure in slope for sustainable stability in the long run.